The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/10406387211003551
|View full text |Cite
|
Sign up to set email alerts
|

Review of methods for the detection of Lawsonia intracellularis infection in pigs

Abstract: Lawsonia intracellularis is an obligate intracellular bacterium associated with enteric disease in pigs. Clinical signs include weight loss, diarrhea, and, in some cases, sudden death. The hallmark lesion is the thickening of the intestinal mucosa caused by increased epithelial cell replication, known as proliferative enteropathy. The immune response to L. intracellularis is not well defined, and detection of the infection, especially in the early stages, is still a significant challenge. We review here the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 95 publications
(195 reference statements)
0
13
0
1
Order By: Relevance
“…Experimental infection studies have shown that at least five days of intracellular replication are necessary to reach detectable levels of L. intracellularis by IHC or in situ hybridization (ISH). The antigen could be detected up to 14 days post-infection [ 5 ]. It is plausible that the examination of more than one pig would have increased the probability of detecting cases with antigen detectable by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental infection studies have shown that at least five days of intracellular replication are necessary to reach detectable levels of L. intracellularis by IHC or in situ hybridization (ISH). The antigen could be detected up to 14 days post-infection [ 5 ]. It is plausible that the examination of more than one pig would have increased the probability of detecting cases with antigen detectable by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of investigation for diagnosing PE in swine are available, each with its strengths and limitations [ 5 ]. The clinical presentation alone is inadequate for diagnosis as it overlaps with other intestinal pathogens such as Brachyspira hyodysenterie, Brachyspira pilosicoli , Salmonella enterica , Escherichia coli , and PCV2 [ 2 , 5 ]. The gross features of PE are also shared with PCV2 enteritis [ 2 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Für den direkten Erregernachweis am lebenden Tier eignet sich die Untersuchung von Kot mittels quantitativer Polymerase-Kettenreaktion (qPCR), um eine intrazelluläre Vermehrung des Erregers im Tier und damit eine mögliche Beeinträchtigung des Tieres festzustellen. Serologische Untersuchungen bei heranwachsenden und adulten Schweinen beweisen ausschließlich eine Exposition zum Erreger und eignen sich darum lediglich zum Screening in Herden oder zur Feststellung des Infektionszeitpunktes, jedoch nicht zur Diagnose einer gegenwärtigen Erkrankung der Tiere [4]. Weiter ist dabei zu beachten, dass maternale Antikörper bis etwa zur 5.…”
Section: Diagnostikunclassified